Impact of implicit feedback channel in cooperative relay networks - Madhukumar, A. S. (2013)
In a multi-node network, cooperation among nodes is an effective means to enhance coverage and potentially increase the capacity. For such systems, schemes based on incremental relaying have great potential to improve the spectral efficiency by adapting the transmission to time varying channel conditions. The performance enhancement brought about by the presence of relays in such incremental relaying based cooperative systems is dependent on the level of cooperation (based on the relay information quality) and on coordination among the nodes. Coordination is achieved through the use of feedback channels, which incurs significant bandwidth penalty and brings down the spectral efficiency. In order to mitigate this, one can exploit an implicit feedback channel available due to broadcast nature of relay transmissions. Instead of using dedicated feedback channels, the implicit feedback channel is used to measure the relay information quality. Based on this information, the transmitter (source/relay) for the additional coded (redundancy) bits is determined. Such a mechanism enhances the reliability as it ensures the availability of correct information at the destination node for decoding. This paper studies the impact of such an implicit feedback channel by employing powerful codes which exhibit inherent incremental redundancy features, such as rate-compatible codes (rate-compatible punctured convolutional (RCPC) codes and punctured low-density parity-check (LDPC) codes) and rateless codes (Luby Transform (LT) codes). Theoretical analyses of the proposed scheme are presented, and supported with results from extensive simulation studies.